Relationship between Goal Orientation and Procrastination in High School Students: Mediating Role of Attributional Styles - Kobra Akhlaghinia; Majid Barzegar; Soltanali Kazemi (Iranian Evolutionary Educational Psychology Journal)
Objective: The current investigation sought to elucidate the mediating function of attributional styles within the context of the relationship between goal orientation and procrastination among final-year students enrolled in government high schools in Yasuj city, Iran. Methods: The methodological framework employed for this research was a descriptive-correlational design. The statistical population encompassed all final-year students attending government high schools in Yasuj city, amounting to a total of 4,000 students in the year 2021. From this population, a sample of 300 students was extracted utilizing a multi-stage cluster sampling technique. For the purpose of data collection, the researchers administered the Goal Orientation Questionnaire, the School Procrastination Scale, and the Attributional Style Questionnaire (ASQ). Results: The findings indicated that mastery-approach and performance-approach goal orientations exerted a positive direct influence on optimistic attributional styles while simultaneously demonstrating a negative impact on pessimistic attributional styles. Conversely, the performance-avoidance and mastery-avoidance goal orientations were found to have a positive and direct effect on pessimistic attributional styles. Furthermore, optimistic attributional styles exhibited a negative and direct relationship with procrastination, in contrast to the positive and direct association observed between pessimistic attributional styles and procrastination. Additionally, goal orientation was found to have a direct and significant impact on mitigating procrastination through the mediation of optimistic attributional styles. Conclusions: Based on the findings, it can be inferred that attributional styles and goal orientation are pertinent variables related to student procrastination, necessitating their consideration in the formulation of interventions designed to alleviate procrastination among students.